Religusitas Memoderasi Pengaruh Karakteristik Internal dan Eksternal Perilaku Dysfunctional Audit di Kantor Akuntan Publik - Jhista Wiguna, I Gusti Made; Ariyanto, Dodik (E-Jurnal Akuntansi, 2023)
The aim of this research is to analyze the role of religiosity in moderating internal locus of control, professional commitment, and time budget pressure on the dysfunctional behavior of auditors at the Bali Province Public Accounting Firm. Data collection was carried out using a questionnaire. The number of samples used was 57 auditors with a saturated sampling method. The data analysis technique in this research uses the PLS-SEM approach with the help of SmartPLS version 4. Based on the results of hypothesis testing, it was found that internal locus of control and professional commitment had a negative influence on dysfunctional audit behavior. Meanwhile, time budget pressure has a positive effect on dysfunctional audit behavior. The results of the moderation effect test show that religiosity is able to strengthen the influence of professional commitment on dysfunctional audit behavior. However, internal locus of control and time budget pressure are unable to moderate the influence of dysfunctional audit behavior. Keywords: internal locus of control; professional commitment; time budget pressure; religiousity; dysfunctional audit behavior